Changes in human placental oxygenation during maternal hyperoxia estimated by blood oxygen level‐dependent magnetic resonance imaging (BOLD MRI). (2nd September 2013) - Sørensen, A.; Peters, D.; Fründ, E.; Lingman, G.; Christiansen, O.; Uldbjerg, N.
ABSTRACT: Objectives: To investigate changes in human placental oxygenation during maternal hyperoxia using non‐invasive blood oxygen level‐dependent (BOLD) magnetic resonance imaging (MRI). Methods: Eight healthy pregnant women with uncomplicated singleton pregnancies at gestational weeks 28–36 were examined with BOLD MRI, over two consecutive 5‐min periods of different oxygenation: first normoxia (21% O2 ) and then hyperoxia (12 L O2 /min), achieved by controlling the maternal oxygen supply with a non‐rebreather facial mask. Selecting three slices showing cross‐sections of the central part of the placenta, we investigated total placental oxygenation by drawing regions of interest (ROIs) covering the entire placenta, and regional placental oxygenation by drawing smaller ROIs in the darker and brighter areas of the placenta. For each ROI, the difference in BOLD signal between the two episodes was determined and the percentage increase in BOLD signal during hyperoxia (ΔBOLD) was calculated. Results: In the BOLD image, the normoxic placenta appeared heterogeneous, with darker areas located to the fetal side and brighter areas to the maternal side. During hyperoxia, the placenta became brighter and the structure more homogeneous, and the BOLD signal of the total placenta increased (ΔBOLDtot, 15.2 ± 3.2% (mean ± SD), P < 0.0001). The increase was seen predominantly in the dark areas in the fetal part of the placenta (ΔBOLDfet, 32.1 ± 9.3%) compared with in the bright areas in the maternal part of the placenta (ΔBOLDmat, 5.4 ± 3.5%). Conclusion: During hyperoxia, placental oxygenation was increased predominantly in the darker placental areas, which, given their anatomical location, represent the fetal circulation of the placenta. To our knowledge, this is the first study to successfully visualize changes in placental oxygenation using BOLD MRI. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.